Efektivitas Pemberian Dana Usaha Terhadap Pemberdayaan Ekonomi Perempuan (Studi Kasus Koperasi Wanita Mayangsari 38b Banjarrejo) - Wati, Saprida; Budiarti, Riskha Tri; Susanto, Rindang (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2023)
Women's empowerment through business financing is the main focus of this research. The research was conducted using a qualitative approach and a case study in Banjarrejo 38B Village, with Assifa Mulya Women's Cooperative as the research subject. Data were collected through interviews with cooperative members who have received business financing, as well as document analysis related to cooperative activities. The results show that the provision of business financing by the cooperative has succeeded in increasing the productivity of its members and improving family living standards. The concept of women's empowerment, which consists of three levels, namely enabling, empowerment, and protection, is the theoretical basis for this research. In addition, the results also measure the effectiveness of the program by considering indicators of program understanding, goal achievement, timeliness, and actual change. Nevertheless, there are problems related to the use of funds that are not in accordance with the purpose of the loan, which affects the sustainability of the program. The implication of this study is the importance of better supervision of the use of funds and more intensive mentoring of members to ensure that loans are optimally used for business purposes. As such, this research makes an important contribution in strengthening the understanding of the importance of women's empowerment through the provision of business financing by cooperatives.